After the Cold War: Does international trade and financial law matter? - Breskovski, Vassil (European University Institute, 1998)
Keywords: Cold War; Commercial law; Foreign economic relations; International Trade; International business enterprises; International economic relations; Post-communism; Russia (Federation)

L'ordre public économique dans un pays en développement : l'exemple du Sénégal - Kanté, Alassane (Université Cheikh Anta Diop, 1998)
La Thèse portant sur l’ordre public économique a pour objet d’appréhender l’un des concepts juridiques les plus significatifs et les plus aptes à assurer le développement économique et social d’un pays sous-développé comme le Sénégal : il s’agit, en l’occurrence, du droit économique qui est une donnée essentielle de toutes les politiques économiques actuelles. Pour ce faire, l’étude passe en revue la synthèse des différents ordres publics dans diverses matières juridiques pour aboutir subséquemment à la problématique suivante : l’ordre public économique serait-il la résultante de l’ensemble de ces différents ordres publics ou a-t-il une définition et une finalité propres ? Dans la perspective d’une réponse à la problématique posée, l’axe principal de nos réflexions tient compte de l’économie et du droit économique. Ainsi, si l’économie repose toujours sur une politique, il s’ajoute que ce sont les options politiques qui lui impriment son caractère. On en déduit que ces orientations politiques seront tantôt la direction, tantôt la protection. Ces deux préoccupations pouvant être aussi distinctes qu’intimement liées. Cette idée directrice a sous-tendu le fil conducteur de nos réflexions pour examiner l’accomplissement de cette double fonction de l’ordre public économique dans un droit qui cherche à promouvoir le développement économique et social. Enfin, la réponse majeure apportée à la problématique posée est que la synthèse des résultats des travaux révéleront positivement que la distinction entre l’ordre public de protection et l’ordre public de direction au sein de l’ordre public économique constitue effectivement un objet scientifique d’étude et de réflexion. À cet égard, la réalisation d’un tel résultat a été rendue possible grâce à la prise en compte de la double fonction de direction et de protection située dans le contexte d’un pays en développement, comme le Sénégal dont la législation économique actuelle s’inspire d’un libéralisme qui n’est pas sans danger pour les acteurs économiques nationaux et les consommateurs.
Keywords: Droit économique; Ordre public économique; Sénégal

States and markets : regulatory competition and the public law of banks - Padrós Reig, Carlos (European University Institute, 1997)
One of the most immediate questions that could be raised is that of the topic. Why banks?. Banks are a part of the economy which is especially prone to regulatory competition. Increasing financial globalization makes it difficult to maintain regulatory barriers and those remaining create costs that are avoided by regulatory arbitrage. Banks’ raw material is capital which is a highly mobile element. On the top of that, the longstanding experience of the US in the field, should be of some usefulness. Finally, banks are attractive since the European Union, by means of the Second Banking Directive, has undertaken a decisive step towards liberalisation. Regulatory competition in this field will be able to give us some clues into the direction of services regulation in general, and into the new institutional dimension of the Union. However, banks are only one type of financial actors. Securities and insurance industry are gradually occupying spaces traditionally reserved to banks - namely deposit collection and lending - and conversely, banks are extending their product range to cover securities and insurance activities, and are experiencing a process of disintermediation. Hence, it is increasingly impossible to distinguish among financial actors. Concentrating in one of them is just a research need in order to keep the study under manageable dimension. Still, banks remain a legally different industry because of their position in the economic gear and in the payment system. What could actually be questioned is the future of banks themselves or at least their different legal treatment In any case, the topic of financial services regulation is too large to be covered as a whole, so some subdivision is necessary. This has to be done acknowledging that divisions may not correspond to the reality of the marketplace.
Keywords: Banks; Competencia; Competition law; Law of Banks; Regulation

La tarjeta de crédito. Vol. 1 - Núñez Lozano, Pablo Luis (Universidad de Sevilla, 1996)
La Tesis Doctoral tiene por objeto trazar el aspecto de conjunto del fenómeno de la tarjeta de crédito. Tras la delimitación de la figura, realizada a partir de la consideración de sus orígenes y evolución, y luego de tratar del marco jurídico (Derecho Positivo Español, actuaciones de la Comunidad Europea, trabajos de la comisión de las Naciones Unidas para el Derecho Mercantil internacional), se estudian sus caracteres documentales: Idoneidad Legitimadora e Intransmisibilidad. Asimismo se presta atención a las posiciones jurídicas documentalmente representadas por la tarjeta de crédito y a los procedimientos de utilización, distinguiendo entre sus modalidades básicas: las denominadas tarjetas de crédito "bilaterales" y las "trilaterales".
Keywords: Carte de crédit; Credit cards; Tarjetas de crédito

La tarjeta de crédito. Vol. 2 - Núñez Lozano, Pablo Luis (Universidad de Sevilla, 1996)
La Tesis Doctoral tiene por objeto trazar el aspecto de conjunto del fenómeno de la tarjeta de crédito. Tras la delimitación de la figura, realizada a partir de la consideración de sus orígenes y evolución, y luego de tratar del marco jurídico (Derecho Positivo Español, actuaciones de la Comunidad Europea, trabajos de la comisión de las Naciones Unidas para el Derecho Mercantil internacional), se estudian sus caracteres documentales:Idoneidad Legitimadora e Intransmisibilidad. Asimismo se presta atención a las posiciones jurídicas documentalmente representadas por la tarjeta de crédito y a los procedimientos de utilización, distinguiendo entre sus modalidades básicas: las denominadas tarjetas de crédito "bilaterales" y las "trilaterales".
Keywords: Carte de crédit; Credit cards; Tarjetas de crédito

La tarjeta de crédito. Vol. 2 - Núñez Lozano, Pablo Luis (Universidad de Sevilla, 1996)
La Tesis Doctoral tiene por objeto trazar el aspecto de conjunto del fenómeno de la tarjeta de crédito. Tras la delimitación de la figura, realizada a partir de la consideración de sus orígenes y evolución, y luego de tratar del marco jurídico (Derecho Positivo Español, actuaciones de la Comunidad Europea, trabajos de la comisión de las Naciones Unidas para el Derecho Mercantil internacional), se estudian sus caracteres documentales:Idoneidad Legitimadora e Intransmisibilidad. Asimismo se presta atención a las posiciones jurídicas documentalmente representadas por la tarjeta de crédito y a los procedimientos de utilización, distinguiendo entre sus modalidades básicas: las denominadas tarjetas de crédito "bilaterales" y las "trilaterales".
Keywords: Carte de crédit; Credit cards; Tarjetas de crédito

Two essays on political influence and the regulation of financial markets - Eckel, Doug (Virginia Tech, 1996)
I examine two potential instances of rent-seeking in financial markets in the 1980s. In the first essay I test whether managers engage in political activity designed to influence federal regulation of the market for corporate control. In the second, I examine whether firms in the financial services sector attempt to affect bank deregulation. Using Federal Election Commission data, I find campaign contributions by corporate political action committees (PACs) are negatively related to levels of inside ownership, my main proxy for managerial vulnerability to hostile tender offers. Contribution patterns for firms with less than 20% insider ownership are relatively highly correlated, and differ from those of firms with greater than 20% inside ownership. Low inside ownership firms have slightly higher levels of contributions to legislators on particular House and Senate committees proposing relevant legislation. However, when I analyze the impact of contributions on legislator support for regulation I find no statistical support for a theory of vote-buying. I conclude that corporate political behavior is tied to levels of inside ownership, and comprises an alternate index of manager-shareholder conflict. Using a similar approach to analyse the financial services industry, I also find significant patterns in political action committee (PAC) campaign contributions for depository (commercial bank and thrift) and non-depository (brokerage and insurance) sectors of the financial services industry during the 98th Congress (1983-84). Contributions by depository firm PACs appear not only to purchase access to legislators serving on important banking committees crucial to their interests, but are also a significant determinant of votes for repealing sections of the Glass-Steagall Act. Nondepository contributions do not appear to influence votes directly, even though the brokerage and insurance sectors effectively lobbied House Banking Committee chairman Fernand St Germain to enforce the regulatory status quo. When I measure the rents at stake in the legislation using a two-factor market model event study approach, I find that the passage of legislation in the Senate had a positive affect on depository firm returns, implying the sector's lobbying effort was justified. However non-depository PACs lobbied just as extensively, and did not experience significant abnormal returns over the same event period, even though this round of deregulation should have been a zero-sum game between the affected sectors of the industry. I then measure the correlation between the market value impacts of new legislation and contribution amounts for individual firms within the sectors. I find rents are correlated with political activity, even for firms in the non-depository sectors.
Keywords: Corporate control; Financial institutions; Financial markets; Regulation

Análisis jurídico de la auditoría de cuentas - Jané Bonet, Juan (Universitat de Barcelona, 1994)
Las cuestiones que nacen de las relaciones entre el Derecho Mercantil, la Contabilidad y la Auditoría resultan necesariamente atractivas para quien desarrolla su actividad en temas donde ambas disciplinas están estrechamente unidas, y tienen influencias recíprocas y se prestan mutuamente un auxilio para la solución de determinados problemas. Por un lado, al ser la Contabilidad materia esencial de la Diplomatura de Ciencias Empresariales, es natural que quien desempeña una titularidad de una materia jurídica se vea fuertemente influenciado por las repercusiones que la contabilidad produce en la disciplina que él profesa. Si además le unimos el ejercicio profesional donde ambas materias conviven en amigable armonía, aunque presentando siempre cuestiones prácticas de innegable interés, es lógico que quien les escribe esté fascinado por seguir adelante en el análisis jurídico de las vinculaciones entre las citadas tres materias. Tras lo dicho, resulta oportuno reflexionar aquí acerca del objeto inmediato de este trabajo, que no es más que la exposición del nuevo régimen jurídico de la auditoría de cuentas en el Derecho Español vigente, desde una perspectiva netamente jurídico-mercantil, relacionado la misma con otros campos jurídicos y contables, y estudiando asimismo las instituciones de la armonización contable y de auditoría, y sus antecedentes históricos. Problema más complicado es determinar el método jurídico utilizado. JIMENEZ DE PARGA, señala que el método es el camino que se sigue en la tematización de la realidad que se analiza. Así el método debe ser diferente y el apropiado para cada trabajo y, es más, en un estudio debe ser un producto científico nuevo, o al menos diferente. En el campo jurídico podemos trabajar en dos grandes vertientes metodológicas (dogmática-formalista y empírico-sociológica). Ambas opciones, sin ser antagónicas, pueden hacerse compatibles en la formulación de las hipótesis jurídicas. A mi entender el estudio que tienen en sus manos desarrolla ambas, es decir, en la primera y la segunda parte se ha utilizado la metodología empírica-sociológica y en la tercera parte la dogmática-formalista. Respecto al método operacional me he planteado inicialmente los temas más generales hasta llegar a los aspectos concretos y específicos del problema realizándose por el camino deductivo. A mayor abundamiento, se ha utilizado un método de análisis y se ha intentado descomponer la auditoría de cuentas en sus diversos aspectos, por lo que debe ser considero un estudio jurídico-descriptivo. El estudio se divide en tres partes que se vertebran en sus correlativos capítulos, apartados, epígrafes, subepígrafes y letras. Por último, sólo me queda por añadir que las notas a pie de página están numeradas de forma independiente en cada parte, y recogen tanto razonamientos marginales del texto principal corno las citas que se expresan el estado de la doctrina.
Keywords: Audit; Audit de compte; Auditoria de comptes; Ciències Jurídiques; Comptabilitat; Comptabilité; Dret Mercantil; Econòmiques i Socials

L'acquisition à crédit des biens d'équipement personnel en droit ivoirien - Kassia, Bi Oula (Université de Nice Sophia-Antipolis, 1993)
L'étude porte sur les techniques juridiques que permettent à un particulier d'acquérir à crédit des biens durables pour son usage personnel ces techniques sont étudiées en relation avec les biens dont elles financent l'acquisition. L'analyse des différentes techniques (première partie), met en lumière l'insuffisance des règles légales et jurisprudentielles régissant la matière. Les rapports des parties sont réglés par les clauses des contrats types. Ceux-ci privilégient la protection du créditeur. Le crédit exerce une influence sur l'ensemble de l'opération d'acquisition (deuxième partie). A cet égard, l'étude du crédit affecte (crédit-bail, prêt lié), permet de constater l'indépendance du contrat de financement et du contrat d'acquisition. Néanmoins, l'acquéreur insatisfait (défaut de délivrance), trouve dans le droit commun un moyen de se protéger : responsabilité, théorie de l'apparence.
Keywords: Achat; Automobiles; Crédit à la consommation; Crédit-bail; Équipement industriel

Pour un nouveau régime d'imposition des bénéfices des sociétés dans les pays de la C.E.A.O - Sarr, Marie-Pierre Rokhayatou (Université de Dijon, 1986)
Keywords: Imposition; Impôt sur le revenu; Société commerciale; Taxation

L'imposition des revenus des entreprises étrangères en Côte d'Ivoire - Togba, Zogbèlèmou (Université Paris 7, 1984)
Keywords: Entreprise étrangère; Imposition; Impôt; Revenu; Taxation

Fonctionnement et technique des banques en Afrique de l'Ouest - Touré, Amadou (Université Paris 5, 1978)
Keywords: Afrique de l'Ouest; Banque (fonctionnement); Technique bancaire

The raising and maintenance of capital : a comparative study of some problems in the law of corporation finance - Ponnuswami, K. (McGill University, 1969)
This the sis is an in-depth comparative study and critical examination of several wide-ranging problems in the law of corporation finance of Britain and the principal jurisdictions of Canada and the United States of America. The problems examined include inadequate Capitalization, Stock-watering, Reduction of Capital, Purchase by a Corporation of its Shares, and Dividends. The the sis examines the trends and patterns in the different jurisdictions and appraises their merits and defects. The study concludes that the conceptual ambiguities and practical difficulties which abound in the laws of corporation finance are aggravated by the failure of the law to work out rational rules based on a clear and unifying policy for the raising and maintenance of capital. The necessity for such a policy is advocated in view of the inadequacy of the existing institutions and devices for the protection of the multifarious interests involved in corporate business enterprises. Cette thèse se présente sous la forme d'une étude comparative en profondeur et d'un examen critique de quelques problèmes du droit des corporations financières de Grande Bretagne et des principales juridictions du Canada et des Etats-Unis d'Amérique. Y sont étudiés entre autres l'insuffisance de capital, la dilution de capital, la réduction de capital, le rachat de ses actions par une corporation et les problèmes concernant les dividendes. On y examine ensuite les tendances et positions de ces différentes juridictions, pour en évaluer les mérites et les défauts. En conclusion cette étude montre que les ambiguités conceptuelles et les difficultés pratiques qui abondent dans le droit des corporations financières sont aggravées par l'insuffisance de la loi à élaborer de règles rationnelles, basées sur une politique claire et uniforme de souscription et de maintien du capital. La nécessité d'une telle politique semble évidente lorsque l'on considère l'imperfection des institutions actuelles et des moyens de protection des multiples intérêts impliqués dans les corporations commerciales.
Keywords: Capitalization; Corporations; Finance; Reduction of capital; Shares